Professor Jian Ge: the road to the success of scientific research - SelimanHelen X.; WangMolly J. (眼科学报; 卷 31, 编号 1 (March 2016): 《眼科学报》, 2015)
Professor Jian Ge ( Figure 1 ) currently is member of standing committee of the Asia Pacific Glaucoma Society, Honorary Chairman of the Chinese Ophthalmologic Society, Vice chairman of the Chinese Eye Doctor Association, Former Chairman of the Chinese Glaucoma Society, Honorary Lifetime Director of State Key Laboratory of Ophthalmology, Chairman of Guangdong Eye Doctor Association, member of standing committee of the Evidence-Based Medicine Committee of the Chinese Doctor Association, Editor-in-Chief of Eye Science and Molecular Vision, Vice Editor-in- Chief of Chinese Journal of Ophthalmology and Chinese Journal of Experimental Ophthalmology .